Removal of nutrients and bioelectricity generation from institutional wastewater using constructed wetland-microbial fuel cell - Kenatu Angassa; Tolesa Getu; Mikiyas Abewaa (Results in Engineering)
This study evaluated the removal of nutrients from institutional wastewater and the generation of bioelectric power using a microcosm-scale constructed wetland system integrated with a microbial fuel cell (CW-MFC). The research explored the impact of vegetation on both bioelectric production and wastewater treatment within the wetland matrix. Results indicated that the CW-MFC system with vegetation outperformed the unplanted system in terms of treatment efficiency. The planted modules achieved average total nitrogen (TN) and total phosphorus (TP) removal efficiencies of 94.6 % and 90.0 %, respectively, compared to 90.59 % and 83.5 % in the unplanted system. Notably, the CW-MFC planted with Scirpus atrovirens exhibited the highest average output voltage (0.648 V) and power density (232 mW/m³). In contrast, the unplanted CW-MFC produced a maximum voltage of 0.537 V and a power density of 220 mW/m³. These findings suggest that Scirpus atrovirens enhances both the treatment efficiency and bioelectricity generation by facilitating microbial activity involved in the biodegradation of organic compounds and improving electron flow from the anode to the cathode. The significant nutrient removal efficiencies and bioelectric power generation demonstrate the potential of using a vegetated CW-MFC system to achieve sustainable wastewater treatment while simultaneously producing renewable energy, thus contributing to more eco-friendly waste management practices